Governance of collaborative system of systems. (2016) - Ireland, Vernon
The objective of the paper is to examine governance of collaborative system of systems (SoSs) and to attempt to extend the definition of governance principles outlined by Old Dominion University (ODU) research. These ideas are particularly important as governments and enterprises attempt to restructure their operations through engaging other agents such as enterprises and other non-government organisations. The ODU strategy for governance, which recognises Beer's viable systems model, however, is primarily designed for a single entity system, such as an enterprise, which is very different from a collaborative SoS, in which multiple organisations have a choice whether to belong. Beer's revised model Team Syntegrity is favoured. Total system integration and critical system practice are included as tools to examine social issues and determine what the real problem is.